Identification of operational risk of embedded Subscriber Identity Module (SIM) technology based on ISO 31000: Systematic Literature Review - Dian Elok Pertiwi; Lien Herliani Kusumah (SINERGI, 2023)
In the current digital era, telecommunications industry technology is growing rapidly, impacting the demands for innovation in the telecommunications operator business. One of them is the change in the size of the Subscriber Identity Module (SIM) card model, which is getting smaller, and the use of embedded SIM (eSIM) technology on smartphones. This study aims to identify operational risk factors from the change in SIM card technology to eSIM. The research method used is the Systematic Literature Review (SLR) method. This study documents and reviews scientific journal papers from scientific databases published from 2015 to 2022 on risk management in the information technology field, following this research's objectives. The results obtained from this study showed that there were 43 journals studied, of which four had the theme of technology-embedded subscriber identity module (eSIM), and 13 discussed risk operations technology